Correlation between the peculiarities of structure and luminescence properties of MgWO4-MgMoO4 system - Mikhailik, V; Vasylechko, L; Kraus, H; Kapustyanyk, V; Panasyuk, M; Prots, Y; Tsybulskyy, V (2010)
The prospects for the use of molybdates and tungstates in the opto-electronic devises prompted studies of the structure, as well as luminescence and scintillation properties of MgWO4-MgMoO4 system. The powder samples of (1-x)MgMoO4xMgWO4 (x = 0; 0.01; 0.05; 0.1; 0.3; 0.5; 0.7; 0.9, and 1.0) were synthesised by the solid state reaction technique at 900°C. The results of the X-ray structure analysis identified three types of crystal structure in the pseudo-binary MgWO4-MgMoO4 system, i. e. β-MgMoO4, cuprosheelite α-MgMoO4, and wolframite MgWO4. It is shown that a single-phase solid solution MgMo1-xWxO4 with β-MgMoO4 structure is formed at x < 0.10, whereas at higher concentration of tungsten the mixture of different phases is created. The phase composition of the sample determines the luminescence spectra; the maximum of the emission band is observed at 520 nm for β-MgMoO4, 590 nm for α-MgMoO4, and 480 nm for MgWO4. A possible correlation between the emission spectra and peculiarities of crystal structure are discussed in terms of the canonical configuration coordinate model. The emission efficiency of magnesium tungstate is found to be highest within the compounds under investigation. The scintillation light yield of MgWO4 at T = 295 K is found to be 0.90±0.15 of that of ZnWO4 and remains high with the decrease of temperature.